Exploring the status of disaster risk reduction focusing coping strategies in Rangpur division of Bangladesh - Rahman, MM; Hiya, HJ; Auyon, ST; Islam, MA (Progressive Agriculture, 2018)
Bangladesh is a low laying country where disaster events are common phenomena almost every year. Same as coastal areas of Bangladesh, the northern areas are now suffering huge events of floods, droughts and riverbank erosion. The main purpose of this study is to determine the practice of disaster coping strategies by the people in the study areas. The study was carried out at Rajibpur sub-district under Kurigram district, Saghatta sub-district under Gaibandha district, Gangachara sub-district under Rangpur district, Aditmari sub-district under Lalmonirhat district and Dimla sub-district under Nilphamari district. Data were collected from a sample of 300 respondents from 5 subdistricts by using interview schedules 12 January 2017 to 19 March 2018. About 80% respondents are dependent on the TV or Radio news for pre-disaster warning and forecasting as well as more than this population loses their property above BDT 50000 in every year due to disaster damage. During flood, the respondents maintain some scoping materials like raising plinth, making scaffold, using moveable cooking materials, taking loan from the Mahajan and sold their non-productive assets. Most of the respondents from various study area follow these kinds of measures and about 63.33% respondents use bamboo or wood for their cooking purpose during flood. About 40% respondents from these study areas are suffered of shelter due to riverbank erosion and they migrate here and there for better life. More than two third of the respondents have no opportunity to get any kind of help or relief from the GOs and NGOs. They are now depending on their own coping strategies. They badly need a new coping strategy for reducing the damage of flood or riverbank erosion. Disaster forecasting, early warning system and community-based flood management can save many lives and properties. For effective disaster management strategies, it could be applied early warning systems and adequate training as pre-disaster strategy and availability of relief and other inputs at acceptable price and loan with flexible conditions as post-disaster strategy. Progressive Agriculture 29 (3): 195-204, 2018